2021
DOI: 10.4081/monaldi.2021.1890
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical factors associated with early hospital Coronovirus disease 2019 deaths in a low middle income setting: A record-based analysis of 20,641 deaths from India

Abstract: Understanding the demographic and clinical characteristics cases and deaths is essential for better clinical and public health management of coronavirus disease-2019 (COVID-19) in resource-limited settings. We analyzed the COVID-19 deaths reported from India, to describe the demographic and clinical characteristics and identify the factors associated with early hospital deaths (within one day of hospitalization) and survival duration. We conducted a record review of the publicly available data on COVID-19 deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…É imprescindível compreender que o entendimento sobre as taxas de mortalidade específicas de uma população terá uma contribuição direta sobre a evitação de desperdícios de recursos e de tarefas, além de colaborar com o planejamento e a priorização de investimentos feitos na saúde. Nos casos de Covid-19, especificar as características clínicas e demográficas das fatalidades ajuda os especialistas em saúde pública a tornar prioritário a ação e direcionar a comunicação para conjuntos populacionais de maior risco (PERIYASAMY et al, 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…É imprescindível compreender que o entendimento sobre as taxas de mortalidade específicas de uma população terá uma contribuição direta sobre a evitação de desperdícios de recursos e de tarefas, além de colaborar com o planejamento e a priorização de investimentos feitos na saúde. Nos casos de Covid-19, especificar as características clínicas e demográficas das fatalidades ajuda os especialistas em saúde pública a tornar prioritário a ação e direcionar a comunicação para conjuntos populacionais de maior risco (PERIYASAMY et al, 2022).…”
Section: Introductionunclassified
“…Ademais, ocorrem outras alterações fisiológicas em idosos, que aumentam essa vulnerabilidade a complicações importantes do quadro infeccioso causado pelo Sars-CoV-2, como diminuição da complacência e da força muscular respiratória, atenuação da produção de líquido surfactante, entre outras alterações(GANDRA et al, 2021).Além das supracitadas alterações fisiológicas em idosos, pode-se explicitar que estes apresentam, muitas vezes, doenças crônicas. Algumas dessas patologias são consideradas comorbidades, as quais agravam as fatalidades em quadros de Covid-19, como diabetes, hipertensão arterial, cardiopatias, doenças pulmonares e alterações cerebrovasculares(GANDRA et al, 2021;PERIYASAMY et al, 2022).Relativo ao sexo dos indivíduos que faleceram por Covid-19, é possível mencionar que a maioria pertencia ao sexo masculino. A gravidade dos casos dessa doença é maior, de forma significativa, em homens do que em mulheres.…”
unclassified
“…A study conducted in Peru, for example, found the most common comorbidities associated with mortality due to COVID-19 were obesity, hypertension, and diabetes mellitus ( 13 ), while in Malaysia or India, most of the deaths due to COVID-19 occurred in individuals with diabetes and hypertension, and in those aged 70 years or older ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%